Uji Efektivitas Beberapa Jenis Ekstrak Daun Tanaman terhadap Perkembangan Ulat Daun Kubis (Plutella xylostella L.) di Laboratorium - PUTU PADMA MAHESWARI; I NYOMAN WIJAYA; MADE SRITAMIN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Effectility of some Extract to Larvae of Plutella xylostella Development in the LaboratoryThe research was conducted in November 2017 to Februari 2018 in Udayana University Plant Pest and Disease Laboratory. The aim of this research is to know the ability of some plant leaf extract to larvae of Diamonback Moth (Plutella xylostella) development in the laboratory. Plant extract materials used in this experiment were leaf of Lantana camara, Chromolaena odorata, Tithonia diversifolia, and Nicotiana tabacum. Process of extracting was done in Laboratory of Genetic Resources and Molecular Biology Faculty of Agriculture Udayana University. This research uses Completely Randomized Design (CRD) with 4 treatment of leaf extract at 10% concentration and 1 without treatment (control), each treatment was repeated 10 times. Observations were made until the larvae does not do activity or until become adult. Testing of four types of plant leaf extracts showed the following results: Each of C. odorata leaf extract, L. camara, T. diversifolia and N.tabacum used as research material had different potential in suppressing P.xylostella development. Application of L. camara, T. diversifolia and N. tabacum on larvae can develop through 4 instars before becoming pupa, treatment with plant leaf extract is most effective to suppress the development of larvae biology P.xylostella is a leaf extract of C. odorata that result were 100% mortality on larvae stase and the lowest is on the treatment of N. tabacum extract were 20%.